Competitive exclusion by autologous antibodies can prevent broad HIV-1 antibodies from arising - Luo, Shishi (Proc Natl Acad Sci U S A, 2015)
The past decade has seen the discovery of numerous broad and potent monoclonal antibodies against HIV type 1 (HIV-1). Eliciting these antibodies via vaccination appears to be remarkably difficult, not least because they arise late in infection and are highly mutated relative to germline antibody sequences. Here, using a computational model, we show that broad antibodies could in fact emerge earlier and be less mutated, but that they may be prevented from doing so as a result of competitive exclusion by the autologous antibody response. We further find that this competitive exclusion is weaker in infections founded by multiple distinct strains, with broadly neutralizing antibodies emerging earlier than in infections founded by a single strain. Our computational model simulates coevolving multitype virus and antibody populations. Broadly neutralizing antibodies may therefore be easier for the adaptive immune system to generate than previously thought. If less mutated broad antibodies exist, it may be possible to elicit them with a vaccine containing a mixture of diverse virus strains.